MicroRNAs in exhaled breath Condensate: Novel non-invasive biomarkers for tuberculosis diagnosis - Jaya, Tak; Bijay, Pattnaik; Divyanjali, Rai; Naveen, Bhatraju; Adwika, P.P.; Sunil, Bangaru; Yadav, Sunita; kumar, Sachin; Kumari, Seetu; Verma, Umashankar; Yadav, Geetika; Dhaliwal, R.S.; et al. (Tuberculosis (Edinburgh, Scotland), 2025)
Tuberculosis remains a significant global health issue. Sputum smear microscopy has low sensitivity, making it difficult to diagnose. Analysis of miRNA from EBC (exhaled breath condensate) offers a potential non-invasive diagnostic method that could improve sensitivity and specificity for TB detection, including extrapulmonary TB (EPTB). EBC was collected from 65 treatment naïve TB patients and 65 healthy controls. miRNA profiling was done on an exploratory set (n = 40) using the qRT-PCR-based miRNome profiler kit, and shortlisted miRNAs were validated in a separate set (n = 25) using qRT-PCR. ROC curves were used to evaluate diagnostic performance. In this study, we identified eight differentially expressed miRNAs in TB vs healthy subjects (seven upregulated, one downregulated). Comparing PTB with EPTB, five miRNAs were upregulated and 68 miRNAs were downregulated in PTB. Between PTB and healthy controls, six miRNAs were upregulated and 16 miRNAs were downregulated in PTB, while in EPTB, 132 miRNAs were upregulated compared with controls. Validation confirmed upregulation of miR-454, miR-139, and miR-143 in tuberculosis. The findings of our study indicate that the expression of miR-143, miR-454, and miR-139 in exhaled breath condensate has strong potential as a non-invasive biomarker for TB diagnosis.